Carbon nanotubes inhibit the free‐radical cross‐linking of siloxane polymers. Issue 12 (23rd January 2014) - Li, Zhuo; Moon, Kyoung‐sik; Lin, Ziyin; Yao, Yagang; Wilkins, Stewart; Wong, C. P.
ABSTRACT Carbon nanotubes (CNTs) are found to inhibit the free‐radical cross‐linking of vinyl‐terminated polydimethylsiloxane (PDMS) by trapping the free radicals in a CNT/PDMS composite. The cross‐linking density values measured by swelling test, equilibrium stress‐strain test, glass‐transition temperature and Raman spectroscopy all decrease with the addition of CNTs. The inhibition effect is shown to be more significant with increased functionality and curvature in the CNTs used. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40355.